L’assistance des ONGs dans les milieux ruraux à l’est du Tchad : cas de world concern development organization au Dar Sila - Brahim Malloum MBODOU (Revue Hybrides)
The Chadian government is having enough trouble building schools and recruiting teachers to cover the entire country. In addition to these difficulties, there is the influx of Sudanese refugees fleeing the war in Sudan. As a result, partners in the education system are supporting the government in rural areas and villages affected by the presence of refugees. One of these partners is the World Concern Developpmnt Organization (WCDO). Nowadays, sustainable community development has become an obligatory reason attached to an appeal to the whole of humanity, if not let’s just say to Man as a whole who deserves a descent and sustainable life. The aim of this study is to assess the impact of World Concern Development Organization’s actions on communities and children’s education. In order to achieve this objective, the methodology adopted is based on interviews and direct observation. The data collected and processed reveal that the absence of education is a negative factor forcing rural communities to remain fragile claimants and prisoners of the best understanding of true development, which cannot come from elsewhere. WCDO’s contribution has improved the population’s level of education. It has enabled parents to understand the need to send their children to school.